Endoscopic treatment of biliary complications following liver transplantation - Gülseren Seven,; Kubilay Çınar,; Ramazan İdilman,; Acar Tüzüner,; Selçuk Hazinedaroğlu,; Selim Karayalçın,; Kadir Bahar, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aims of the present study were to review biliary complications following liver transplantation in a single-center experience, to identify the factors associated with biliary complications, and to evaluate the success of endoscopic and percutaneous treatment in such patients. Materials and Methods: Between January 1994 and June 2010, a total of 176 patients with liver disease underwent liver transplantation; 119 recipients were included in this retrospective analysis. Median posttransplant follow-up period was 49 months. Results: Mean age was 43.0±12.7 years. Living donor liver transplantation (LDLT) and deceased-donor liver transplantation (DDLT) were performed in 71 and 48 patients, respectively. Duct-to-duct anastomosis and Roux-en-Y hepaticojejunostomy were performed in 68 and 51 patients, respectively. The overall incidence of posttransplant biliary complications was 36%; anastomotic biliary strictures were the most common biliary complications (42%), followed by biliary leakage (28%). On logistic regression analysis, duct-duct anastomosis was the only risk factor associated with the development of biliary complications (Odds ratio (OR), 3.346; p=0.005). Endoscopic and percutaneous treatment was successful in the majority of patients (81%), and the remaining 19% recipients underwent surgery for biliary repair. Endoscopic retrograde cholangiopancreatography (ERCP) guided drainage and balloon dilatation with stent placement were the most common treatment modalities. Conclusion: Biliary complications were most frequent after liver transplantation; biliary strictures were the most commonly seen. The use of duct-to-duct anastomosis for biliary reconstruction is a risk factor for the development of biliary complications. Endoscopic and percutaneous treatment was successful in the majority of these patients.